The Common Morpheme and Its Impact on Semantic Multiplicity: A Brief Editor on the Interpretation of the Noble Revelation by Ibn Atiyya as a Model - Abu Reash, Samah Yousef; Arar, Mahdi Asaad (Journal of Arabic Language Sciences and Literature, 2024)
The exchange of morphological forms is a linguistic phenomenon that has been covered by studies. This stems from the fact that the origin in the Arabic language is that each form has a specific meaning, but the reality of this language and its ability to act in different structures, called for some forms to come with the meaning of another form, in order to achieve linguistic benefit. Or the word occurs in a place that does not have a root, so it takes the place of the root, and acquires its characteristics of influence, effect, function, parsing, and construction. This phenomenon appeared clearly in the Holy Qur’an. We see that the Qur’anic context employed the phenomenon of substitution between morphological forms, so the form of the active participle came in the sense of the active participle, and the adjective came in the sense of the noun of the active participle or object. This is because the descriptive template is suitable for performing the semantic role of another template, because it has a kind of flexibility or voluntariness that makes it susceptible to various uses. This position is clearly embodied, especially among the interpreters of the Holy Qur’an, when they interpret a verse whose intended origin or infrastructure can be directed to a meaning different from what its apparent structure contains. Thus, there is no doubt that this exchange between formulas did not occur in a vacuum, as it constitutes a process that takes place within the text. It is the replacement of one element in the text with another element. What is meant by substitution here is that a formula replaces a formula with its meaning without pronouncing it, and there is no dispute that this matter has an effect. It is significant in context, and it contributes to the consistency and coherence of the text, and this is what this chapter will show.
Keywords: morphological common; alternation of morphological forms; the phenomenon of substitution; morphemes; prefixes and suffixes; e exaggeration; lam of gender; lam of covenant; effect in context